SITUATION CENTER OF THE MINISTRY OF DEFENSE OF UKRAINE – A MODEL OF EARLY DETECTION AND ANALYSIS OF CRISIS SITUATIONS IN THE STATE SECURITY SECTOR - Y. О. Zhyvylo (Pressing Problems of Public Administration, 2022)
The article examines the issue of creating and ensuring the functioning of the situation center in the system of the Ministry of Defense of Ukraine. The necessity of creating a specialized organizational structure, one of the main tasks of which is to respond to military cyber threats directly under the general coordination of the National Coordination Center for Cyber Security in cooperation with other actors in the field of cyber security.The ways of creation and functioning of the situation center are analyzed, the list of threats to which the separate structure (or its separate elements) and joint performance of the tasks defined by the provisions with the Situational Center of the Armed Forces of Ukraine during the Armed Forces respond to the crisis situations in the cyberspace of Ukraine.In the context of constant militarization of cyberspace of the national segment, the National Security and Defense Council of Ukraine decided to expand and further develop a single network of situation centers and equip them with unified software and hardware that will increase decision-making efficiency at all levels of government. The reason for this growth is precisely the crisis phenomena, which become long-lasting, and management processes are transformed from “crisis prevention” to, mainly, “crisis management”.Under these conditions, there is a significant problem with the interaction of the network of situational centers not only in the field of national security and defense, but also situational centers of public authorities (reserve, mobile) on one platform in real time.In this situation, in order to achieve interoperability, it is extremely important to systematize uniformity in the use of special software and software and hardware to ensure interoperability, stable and continuous operation, testing, configuration and performance monitoring in decision making and monitoring.It is obvious that the State Service for Special Communications and Information Protection of Ukraine will play one of the key roles in the process of expanding and increasing the capacity of the network of situational centers. It is becoming clear that such centers should be integrated into a single secure network, with the ability to quickly collect information, analyze it and make critical decisions for the state.